The heterogeneity of Pinus yunnanensis plantation growth was driven by soil microbial characteristics in different slope aspects - Zhongmu Li; Yong Chai; Chengjie Gao; Jin Li; Kai Cui (BMC Plant Biology)
Abstract The slope aspect is an important environmental factor, which can indirectly change the acceptable solar radiation of forests. However, the mechanism of how this aspect changes the underground ecosystem and thus affects the growth of aboveground trees is not clear. In this study, Pinus yunnanensis plantation was taken as the research object, and the effects of soil and microbial characteristics on tree growth under different slope aspects and soil depths were systematically analyzed. The tree height (H) and ground diameter (GD) on the sunny slope were 7.64% and 8.69% higher than those on the shady slope. The soil pH, alkaline hydrolyzable nitrogen (AHN), available phosphorous (AP), available potassium (AK), total nitrogen (TN), total phosphorous (TP), and total potassium (TK) were significantly different between the different slope aspects. With the increase in soil depth, the content of organic matter (OM), AHN, AP, and AK decreased. There were significant differences in soil microbial diversity and community structure between the different slope aspects, but there was no significant difference among different soil depths. The abundance of Proteobacteria on a sunny slope was lower than that on a shady slope, and the richness of Firmicutes and Planctomycetota was higher than that in a shady slope. With the increase of soil depth, the richness of Proteobacteria increased, and the richness of Firmicutes and Planctomycetota decreased. The structural equation model showed that the influence of soil bacteria and fungi on soil characteristics was much greater than that on tree growth, and the influence of soil characteristics on tree growth was much greater than that of soil microorganisms. The slope aspect caused the difference of soil microorganisms, further affected the soil characteristics and led to the heterogeneity of aboveground forest growth. The insights gleaned from this study hold the potential to inform the formulation of customized management strategies, thereby enhancing resource utilization efficiency and fostering the vitality of forest ecosystems. Furthermore, this research offers theoretical underpinning for the targeted cultivation of coniferous plantations.